PENGARUH MENONTON SIARAN LANGSUNG SALURAN BTS DI APLIKASI V LIVE TERHADAP MOTIVASI BELAJAR BAHASA KOREA PADA KOMUNITAS BTS FANBASE INDONESIA - Dirayati Rahmatina; Suyanto " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
The effect of social media is the emergence of a change of perception in aperson that may lead to a change in attitude and behavior of the person. The S-Rmodel theory illustrates the mass media communication process that emulates thestimulus and the recipient responds by showing the response. In addition to providinginformation and entertainmen, social media can also affect a person's learningmotivation. One of the media that can generate motivation is V live app. V live app isa live video app that is popular among Korean culture fans. The purpose of this studyis to find out how much effect Watching Live Streaming BTS Channel On V LiveApplication To Motivation Learning Korean Language Of BTS Fanbase IndonesiaCommunity.The method used is quantitative by using sampling technique saturated andthe number of samples of 102 respondents. Researchers collected data withquestionnaires. In this research, researcher use simple linear regression analysis. Toprocess the test questionnaire data is done by using SPSS (Statistical Product andService Solutions) program Windows version 23.The results obtained from the analysis of responses of respondents is theindicator variable X the most dominant is the frequency indicator with the averagevalue of answers is 3.5 in the category agree, while the variable Y indicator with themost dominant indicator is the existence of expectations with an average grade of 3.5answers in the agreed category. Then from the test results of determination coefficienobtainned Rsquare value of 0.454. So it can be concluded that watching livebroadcast BTS channel has an effect of 45.4% on the motivation to learn Koreanlanguage of members BTS Fanbase Indonesia community, and lies within thecategory strong enough.Keyword: effect of social media, Motivation Learning